DISTRIBUTION PATTERN OF THE EXOTIC PLANT (SYNEDRELLA NODIFLORA (L) GAERTN) IN THE REHABILITATION ZONE, RESORT OF WONOASRI, MERU BETIRI NATIONAL PARK - Yennita Dwi April Liana; Hari Sulistiyowati; Arif Mohammad Siddiq (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2021)
Exotic plants are plants that are intentionally or unintentionally included in an area. Based on the results of the 2020 survey, one of the exotic plants found in the Donglo Block Rehabilitation Zone area of Meru Betiri National Park (MBNP) is cinderella weed (Synedrella nodiflora). The objective of this study is to determine the distribution pattern and area of cover of exotic S. nodiflora plants in the research location. Data were collected using a combination method of systematic plot transects measuring 2 x 2 meters which were placed along the transect with a total of 415 plots. The data recorded were the coordinate position of each individual S. nodiflora and the area of the cover. Analysis of distribution pattern data using the Morisita index and visualized with a spatial distribution map using Geographic Information System (GIS). Coverage area analysis was carried out by calculating the percent cover of S. nodiflora. The results of the analysis of the Morisita index showed the value of Iδ = 7.13, which indicates that the distribution pattern of the plants is clustered. In addition, the presence of this species in the study area was occupied 41.7% or 0.85 ha of the total area of 2.04 ha. It shows that this species still did not dominate the area, so it can be said that this species has not yet become an invasive species category in the research location.